The Evaluation of E-Commerce Using the Customer Satisfaction Index and Importance Performance Analysis - Mugi Praseptiawan; Maria Oktarise Natania Gultom; Meida Cahyo Untoro (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2022)
The challenges of e-commerce development pressure every company to develop the appeal of the company's business processes, which will impact high business revenue. Evaluation is essential for a company to improve the assessment of the company's products. The purpose of this study is to evaluate the use of e-commerce applications from people's perspectives and perceptions by specifically identifying indicators that have or have not met user expectations in using them. This study is quantitative research. The variables are attributes of service used derived from the Delone Mclean model. The measurement of user satisfaction level is done using the Customer Satisfaction Index. The data analysis method used is the Importance Performance Analysis (IPA), done by comparing the level of importance and the level of service performance felt by users. The satisfaction index result obtained by the Shopee application is Very Satisfied with a value of 80.23 %, the Tokopedia application obtained a satisfaction index of Satisfied with a value of 78.58%, and the Bukalapak application's satisfaction index is also Satisfied with a value of 73.22%. Importance Performance Analysis (IPA) methods are used to acquire the knowledge of user satisfaction level regarding any factors impacting the e-commerce application's performance level in meeting user satisfaction. The result obtained by the Shopee application for the IPA method is the absence of variables going into the leading priority quadrant. In contrast, the Tokopedia application has four variables, and the Bukalapak application has five variables in the central priority quadrant.